Association Between Enlarged Adenoid and Otitis Media with Effusion in Children - Karim, Abdul; Huq, AHM Zahurul; Salam, Kazi Shameemus; Kabir, ABM Luthful; Akram, Md Shafiul; Haque, Zubaidul (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To assess the association between enlarged adenoid and otitis media with effusion in children. Methods: This cross sectional comparative study was carried out in the Department of Otolaryngology-Head & Neck Surgery in Bangabandhu Sheikh Mujib Medical University, from July 2013 to June 2015. Thirty children with enlarged adenoids (case) and 30 children without enlarged adenoids (control) were included in this study. All patients subjected for history, local physical examination and evaluation of adenoid size by lateral X-ray of post nasal space. Tympanometry and pure tone audiometry are also done. Information’s recorded on a specially designed data sheet. Result: Among 30 case and 30 control, 12 (40.0%) and 2 (6.7%) patient had OME in case and control group respectively, mean age was 9.5 (2.76%) years and 9.96 (2.95%) in case and control group respectively. Male were predominant (70%) than female (30.0%) in cases. Among cases, grade- I was 20.0%, grade II- was 33.3% and grade-III was 46.7%. Hearing loss was found in 14 (46.7%) children. According to tympanometry, type A curve was in 17 (56.7%) children, type B in 9 (30.0%) and type C in 4 (13.3%) cases. Conclusion: Enlarged adenoids can be relevant in the pathogenesis of otitis media with effusion. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 47-53